Fundamentals of Text Clustering - Ojo, Adebola K. (Text Mining Techniques with Applications, Edition 1, 2024)
It describes the process of determining a corpus of text documents' clustering structure and allocating items to the found cluster or clusters). We will discuss the aspects and cases of text clustering; its major groups, steps involved, levels, components and types, and some examples.